Дослідження впливу методу агрегації на характеристики динамічної системи - Демків, Л. І. (НТУ "ХПІ", 2013)
The survey was conducted on the example of two-mass model of electric arc furnace. At synthesis of Takagi-Sugeno fuzzy controller arc voltage and the output voltage thyristor converter are fuzzified and other variables of the state vector are not. The main known methods of aggregation are considered. The obtained results testify that the impact of the choice of aggregation method and its pa- rameters on the behavior of the system is missing, despite that the output of the regulator is different for each method.
Keywords: електромеханічні системи; нечіткі регулятори; ступені свободи; способи агрегації